Protest Wave and Countermeasures of Fear: Lebanese Act of a Global Drama - A. V. Sarabiev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2020)
The paper examines the dynamics of social protests in Lebanon from October 2019 till March-May 2020 when the government imposed unprecedentedly rigorous restrictive measures to combat the spread of COVID-19 infection. The paper identiﬁes the underlying causes of the protests. The author stresses that from the very beginning socio-economic demands of protestors addressed to the executive power (particularly, to grapple with the rising income inequality) were accompanied by calls for democratization on the secular principles and elimination of political confessionalism. At the same time, the author outlines certain speciﬁcs of popular uprisings in Lebanon that distinguish them from simultaneous protests in other countries, namely their supra-ethnic, supra-religious and non-partisan character and their remarkable coherence and coordination, given the lack of overall leadership. The author emphasizes that the subsequent change of government has not brought, however, signiﬁcant changes the protestors hoped for. The new Cabinet was not free from traditional confessional and political bias, whereas legal and administrative measures undertaken by the new government to combat the pandemic were, apparently, also aimed at ‘freezing’ the current situation favorable for both the parliamentary majority and the government. In particular, the recent laws and regulations reﬂect the Government’s desire to prevent the resumption of protests equivalent to those of the fall of 2019. All these measures did not face serious resistance, even though the economic situation of the population has worsened, and many people have lost their livelihoods. However, the fear of the COVID-19 has proved to be a more eﬃcient means of preventing protests than any punitive measure. The author concludes that the dynamics of inter-party competition even under strict quasi-quarantine measures shows that the hopes of protestors for a genuine transition from a traditional clan and confessional structure of the Lebanese political system to the standards and principles of a developed democracy proved futile.